A Role for the Cytoskeleton-associated Protein Palladin in Neurite Outgrowth - Boukhelifa, Malika (The American Society for Cell Biology, 2001)
The outgrowth of neurites is a critical step in neuronal maturation, and it is well established that the actin cytoskeleton is involved in this process. Investigators from our laboratory recently described a novel protein named palladin, which has been shown to play an essential role in organizing the actin cytoskeleton in cultured fibroblasts. We investigated the expression of palladin in the developing rat brain by Western blot and found that the E18 brain contained a unique variant of palladin that is significantly smaller (∼85 kDa) than the common form found in other developing tissues (90–92 kDa). Because the expression of a tissue-specific isoform suggests the possibility of a cell type-specific function, we investigated the localization and function of palladin in cultured cortical neurons. Palladin was found preferentially targeted to the developing axon but not the dendrites and was strongly localized to the axonal growth cone. When palladin expression was attenuated by transfection with antisense constructs in both the B35 neuroblastoma cell line and in primary cortical neurons, a reduction in the expression of palladin resulted in a failure of neurite outgrowth. These results implicate palladin as a critical component of the developing nervous system, with an important role in axonal extension.